(untitled) (PerCursos, 2022)
The overlapping union: nature-body-mind-soul-spirit-God; it denotes a sentipensante quality of the conception of the human being that makes it privileged of the other animals. In the present investigation, transepistemes of the complex conception of the human being were supported: nature-body-mind-soul-spirit-God as a research objective. Located in the lines of research: Planetary decoloniality-complexity in relinkage and transepistemologies of knowledge-knowledge and transcomplex transmethodologies. Framework where we imbricate an exquisite complexity of the human being that must be revealed in the planetary decoloniality. We go through the moments: analytical, empirical and propositional. In the latter, anthropoethics is our action in the recivilization of humanity as one of the transepistemic axes of what it is to be a human individual; autonomous and dependent individual. The compassionate essence as another transepistemic axis that transgresses attacking ourselves insofar as we feel that nature is nature, we defend it from our own insanity. Transcendence, that is a transepisteme that issuesanswers to the question: how does the human being want to transcend?